PENGARUH KELENGKAPAN PRODUK DAN LOKASI TERHADAP MINAT BELI MASYARAKAT DI PASAR BULAKAMBA KABUPATEN BREBES - Absor, Ulul; Handayani, Sri Ratih; Amirudin, Amirudin ' (Jurnal Strategik, 2024)
This study is entitled "The Effect of Product Completeness and Location on Public Purchase Interest in Bulakamba Market, Brebes Regency". This study took place at Bualakamba Market, Brebes Regency. This study used multiple linear regression analysis tools, t-test, F-test and coefficient of determination.The results of the analysis of this study are that the completeness of products and location have a partial effect on people's purchasing interest in Bulakamba Market, Brebes Regency, this is proven by the t-test using a 95 percent confidence level and degrees of freedom N-k (97-2) obtained a t-table of 1.6615 and the calculation results in SPSS show X1 = 2.417 and X2 = 3.287 which means that t-count> t-table. This shows that Ho is rejected and Ha is accepted or the completeness of products and location has a significant effect on purchasing interest.And simultaneously the variables of product completeness and location have an effect on people's purchasing interest in Bulakamba Market, Brebes Regency, this is proven by the results of the F Test conducted using a 95 percent confidence level (α = 0.05) and df = n - k - 1, namely 97 - 2 - 1 = 94, obtained Ftable of 3.09. While the calculation results show 13.677. This shows that Fcount> Ftable which means the Ho hypothesis is rejected and Ha is accepted which means that together or simultaneously the independent variables of product completeness (X1) and location (X2) have an effect on purchasing interest (Y). Keywords: Product Completeness, Location, Purchase Interest